2021
DOI: 10.1093/eurheartj/ehab530
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and effects of dapagliflozin on cardiovascular and renal outcomes in patients with type 2 diabetes mellitus in the DECLARE–TIMI 58 trial

Abstract: Aims  We investigated the associations between obesity, cardiorenal events, and benefits of dapagliflozin in patients with type 2 diabetes mellitus (T2DM). Methods and results  DECLARE–TIMI 58 randomized patients with T2DM and either atherosclerotic cardiovascular (CV) disease or multiple risk factors to dapagliflozin vs. placebo. Patients were stratified by body mass index (BMI, kg/m2): normal (18.5 to <25), overweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 20 publications
5
19
0
3
Order By: Relevance
“…Relative benefits of dapagliflozin were observed across the spectrum of BMI, and within BMI strata, among women and men and participants with and without diabetes. Absolute benefits of dapagliflozin on the composite cardiovascular endpoint were highest in participants with grade 2/3 obesity, confirming findings recently published by Oyama et al from the DECLARE‐TIMI 58 trial 29 . We observed similar results across other, exploratory composite endpoints, including the traditional major adverse cardiovascular event (MACE) endpoint of cardiovascular death or non‐fatal myocardial infarction or stroke.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Relative benefits of dapagliflozin were observed across the spectrum of BMI, and within BMI strata, among women and men and participants with and without diabetes. Absolute benefits of dapagliflozin on the composite cardiovascular endpoint were highest in participants with grade 2/3 obesity, confirming findings recently published by Oyama et al from the DECLARE‐TIMI 58 trial 29 . We observed similar results across other, exploratory composite endpoints, including the traditional major adverse cardiovascular event (MACE) endpoint of cardiovascular death or non‐fatal myocardial infarction or stroke.…”
Section: Discussionsupporting
confidence: 90%
“…Absolute benefits of dapagliflozin on the composite cardiovascular endpoint were highest in participants with grade 2/3 obesity, confirming findings recently published by Oyama et al from the DECLARE-TIMI 58 trial. 29 We observed similar results across other, exploratory composite endpoints, including the traditional major adverse cardiovascular event (MACE) endpoint of cardiovascular death or non-fatal myocardial infarction or stroke. Serious adverse events were seen more frequently among obese participants, although rates were numerically lower in participants randomized to dapagliflozin within each BMI category.…”
Section: Discussionsupporting
confidence: 68%
“…In recent years, several large clinical trials showed that SGLT2i displayed excellent cardiorenal protective effects in patients with and without diabetes. 7 , 8 , 9 , 10 Because SGLT2 mainly locates in the proximal tubules, its lowering BP and cardiorenal protective effect is thought to depend on its role in promoting urinary sodium and glucose excretion and weight loss. 44 , 45 , 46 In this study, canagliflozin significantly reduced BP in SS with hypertension but not in SS‐19 BN .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new series of antidiabetic drugs, SGLT2 (sodium‐glucose cotransporter 2) inhibitors (SGLT2i), including canagliflozin, dapagliflozin, and empagliflozin, display impressive renal and cardiovascular benefits and reduce all‐cause and cardiovascular death in patients with and without diabetes from several large‐scale clinical trials. 7 , 8 , 9 , 10 The potential mechanisms that account for the cardio‐beneficial effect of SGLT2i might include lowering plasma volume, lowering blood glucose, increasing urinary sodium excretion, and reducing renin‐angiotensin system activation, all of which might help to lower BP. 11 However, it remains elusive whether SGLT2i might directly act on vascular function and BP.…”
mentioning
confidence: 99%
“…The investigators did not find a significant difference between the strategies in reducing all-cause mortality or cardiopulmonary hospitalizations in this high-risk group. The possible reasons for this are multifactorial, notwithstanding the wider strain coverage conferred by the standard-dose quadrivalent vaccine [ 59 , 60 ••].…”
Section: Cardioprotective Effects Of Influenza Vaccinesmentioning
confidence: 99%